Analisis Karakteristik Sektor Pariwisata Kota Balikpapan - Priandini, Difa Oktavia; Syafitri, Elin Diyah; Mustofa, Umar; Astha, Dwinsani Pratiwi (COMPACT: Spatial Development Journal, 2023)
Tourism has an important role in developing a city. This research aims to analyze the characteristics of the tourism sector in Balikpapan City. The city of Balikpapan has a lot of potential in the tourism sector with 88 tourist attractions categorized into 7 types, namely marine tourism, historical tourism, nature/forest tourism, artificial tourism, culinary tourism, shopping tourism and religious tourism. This type of research is qualitative research with a descriptive approach. This research identifies the characteristics and distribution of tourist attractions in Balikpapan City, providing a comprehensive picture of the condition of the tourism sector. The results of this research are the characteristics of the Balikpapan City tourism sector.